Ethnicity and Deprivation are Associated With Blindness Among Adults With Primary Glaucoma in Nigeria: Results From the Nigeria National Blindness and Visual Impairment Survey. Issue 10 (October 2016) - Kyari, Fatima; Wormald, Richard; Murthy, Gudlavalleti V.S.; Evans, Jennifer R.; Gilbert, Clare E.
Abstract : Purpose: We explored the risk factors for glaucoma blindness among adults aged 40 years and above with primary glaucoma in Nigeria. Participants and Methods: A total of 13, 591 participants aged 40 years and above were examined in the Nigeria Blindness Survey; 682 (5.02%; 95 CI, 4.60%-5.47%) had glaucoma by ISGEO's criteria. This was a case-control study (n=890 eyes of 629 persons): glaucoma blind persons were cases and glaucoma not-blind were controls. Education and occupation were used to determine socioeconomic status scores, which were divided into 3 tertiles (affluent, medium, deprived). We assessed sociodemographic, biophysical, and ocular factors by logistic regression analysis for association with glaucoma blindness. Multinomial regression analysis was also performed with nonglaucoma as the reference category. Results: A total of 119/629 (18.9%; 95% CI, 15.9%-22.4%) persons were blind in both eyes; 510 were controls. There was interethnic variation in odds of blindness; age, male sex, socioeconomic status, prior diagnosis of glaucoma, hypertension, intraocular pressure, and lens opacity were associated with glaucoma blindness. Axial length, mean ocular perfusion pressure, and angle-closure glaucoma were associated with blind glaucoma eyes. In multivariate analysis, Igbo ethnicity (OR=2.79; 95% CI, 1.03-7.57) had higher risk as was being male (OR=4.59; 95% CI, 1.73-12.16) and unmarried (OR=2.50; 95% CI, 1.03-6.07). Deprivation (OR=3.57; 95% CI, 1.46-8.72), prior glaucoma diagnosis (OR=5.89; 95% CI, 1.79-19.40), and intraocular pressure (OR=1.07; 95% CI, 1.04-1.09) were also independent risk factors for glaucoma blindness. Conclusion: Approximately 1 in 5 people with primary glaucoma were blind. Male sex, ethnicity and deprivation were strongly associated with blindness. Services for glaucoma need to improve in Nigeria, focusing on poor communities and men.